Up the loyalty ladder : turning sometime customers into full-time advocates of your business - Raphel, Murray, 1928-; Raphel, Neil. (New York : HarperBusiness, 1995)
Everyone is a customer: most of us pick and choose where and how to buy, offering no particular loyalty to any retail source. In Up the Loyalty Ladder, Murray and Neil Raphel reveal how to reach this mass of "occasional buyers," how to convert sales prospects into regular customers, regular customers into loyal clients, and loyal clients into full-time advocates who will actually guide other customers your way. To supplement these strategies for getting customers to come in, buy more, and come back, the Raphels offer concrete media tips to take you every step of the way, including advice on newspaper, radio, and television advertisements as well as direct mail, telemarketing, and in-store promotional events.
Throughout their book, the Raphels illustrate their points with hundreds of anecdotes and examples pulled from their years in business, interviews with some of America's top salesmen, and case studies of such customer-focused businesses as Ben & Jerry's Ice Cream and the children's clothing catalog company Hanna Andersson.
Includes index.
Keywords: Customer relations; Advertising; Consumer satisfaction; Word-of-mouth advertising; Success in business -- United States; Businesspeople -- United States -- Interviews